Asymptotische Entwicklung der Verteilungsgesetze einiger arithmetischen Funktionen - Kubilius, J. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. П. Кубилюс, Асимптотическое разложение законов распределения некоторых арифметических функций J. Kubilius, Aritmetinių funkcijų pasiskirstymo dėsnių asimptotinės formulės